(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to examine the impact of certain economic variables on the ratio of non-performing loans (NPLs) in Iraq. The NPL ratio to total credit is considered a key indicator of financial and banking stability and one of the most prominent global measures of banking asset quality and the strength of the financial system. A high NPL ratio indicates increased financial risks as it reduces bank profitability and liquidity, undermining investor and depositor confidence, which ultimately negatively impacts the country’s macroeconomy. The study utilized quarterly data spanning the period 2016–2024 and applied the Autoregressive Distributed Lag (ARDL) model to analyze the short- and long-term relationships between the variables. The findings revealed that an improvement in the parallel exchange rate and economic growth rate reduces the NPL ratio, while an increase in public debt and inflation rate raises it. This underscores the need for decision-makers to adopt more realistic and effective fiscal and monetary policies to enhance banking sector stability and achieve sustainable economic growth.